KAJIAN BAHASA AS SEBAGAI BAHASA YANG HAMPIR PUNAH DI DISTRIK MAKBON, SORONG, PAPUA BARAT - Abdul Gaffar Ruskhan (SAWERIGADING, 2011)
Indonesia has the biggest properties of language and literature in the world after Papua Nugini. But the number are notsure exactly. Based on recent study of SIL, Indonesian has 742 regional languages. A few of them are almost death, eventhree of them are death surely. Moreover, study of Pusat Bahasa counts around 60 % from the total goals. Among of languagesendangered is As language in Asbaken, Makbon District, Sorongg, West Papua. According to SIL report, thespeakers are about 230persons only. Namely there is big differentiation between SIL reports and result of this research,such as only 13 persons: 25 years old are 4 persons, 25—50years old are 4 persons, and 50 years old are 5personsonly. Based on the amount of speakers, they have only 1 person who still uses the language actively. The death ofAs languagecan be happened because of the young people in the society do not speak the language in daily activity or family communication.It is used by limited speakers above 50 years old. The young generation no longger understands the lexicon andhow to use the language, or even don't comprehend the As language. Indonesia memiliki jumlah bahasa yang terbesar di dunia setelah Papua Nugini. SIL mencatatnyasebanyak 742 bahasa daerah di Indonesia. Sebagian di antaranya menuju kepunahan, bahkan tiga diantaranya telah punah. Sementara itu, kajian yang dilakukan Pusat Bahasa mencatat sekitar 60% darikeseluruhan menuju kepunahan. Salah satu di antaranya adalah bahasa As di Kampung Asbaken, DistrikMakbon, Kabupaten Sorong, Papua Barat. Menurut laporan SIL, bahasa itu memiliki 230 penutur. Halitu berbanding terbalik dengan hasil penelitian yang dilakukan penulis, yakni berjumlah 13 penutur: 4orang 25 tahun, 4 orang berusia 25—50 tahun, dan 5 orang berusia 50 tahun. Dari jumlah penuturitu hanya 1 orang yang aktif berbahasa As. Kepunahan bahasa As itu terjadi, antara lain, bahwa generasimudanya dalam masyarakat As tidak lagi menggunakan bahasa As, baik dalam percakapan sehari-harimaupun dalam komunikasi keluarga. Sementara itu, generasi muda tidak memahami leksikon bahasa Asitu dan bagaimananya dalam berbahasa.